Perfluoroalkylation of Triarylamines by EDA complexes and Ulterior Sensitized [6π]‐Electrocyclization to Perfluoroalkylated endo‐Carbazoles. Mechanistic and Photophysical Studies - Romero Cordero, Ivan Exehomio (2024)
Blue LEDs-irradiation of a mixture of N,N,N',N'-tetramethylethylenediamine (TMEDA) and perfluoroalkyl iodides (RF−I) – Electron Donor Acceptor (EDA)-complex – in the presence of triphenylamines (TPAs) in an aqueous solvent mixture afforded mono-perfluoroalkylated triphenylamines (RF−TPA) in good yields. These RF−TPA were further subjected to acetone-sensitized [6π]-electrocyclization at 315 nm-irradiation affording exclusively perfluoroalkylated endo-carbazole derivatives (RF−CBz) in quantitative yields. Mechanistic studies and photophysical properties of products are studied.